Isobaric vapor-liquid equilibrium of water þ glymes binary mixtures: Experimental measurements and molecular thermodynamic modelling - Crespo, Emanuel (2020)
In this work, new experimental data on the isobaric vapor-liquid equilibria (VLE) of binary aqueous systems, with six different glycol ethers (glymes), some of which are currently used in the Selexol process, were measured at three different pressures, namely 0.05, 0.07, and 0.1 MPa. From the experimental data, the water activity coefficients were estimated using the modified Raoult's law and used to infer about the effect of the glymes structure on their interactions with water. Moreover, using a coarse-grain molecular model previously proposed in the framework of the soft-SAFT equation of state (EoS) for both glycols and glymes, the experimental data were successfully correlated with a single state-independent binary interaction parameter and average absolute deviations from the experimental data of 1.30 K. Furthermore, the model was used in a predictive manner to obtain the water activity coefficients in the whole composition range, providing useful insights into the systems non-ideality.